The Narrative of Democracy in Classical Arabic Literature: According to Ibn al-Daya in al-Mokafat - Delshad, Sharam (Indonesian Journal of Islamic Literature and Muslim Society, 2023)
This study explores the complexity and narrative of democracy in classical Arabic literature through the lens of Ibn al-Daya's "al-Mokafat." The research addresses how Ibn al-Daya integrates democratic principles into his storytelling by highlighting the political and social dynamics of the Tulunid era in Egypt. By adhering to realism, Ibn al-Daya presents the issues faced by ordinary people and various social classes, offering a polyphonic narrative that reflects diverse voices, cultures, and ideas. The analysis reveals that "al-Mokafat" embodies key democratic characteristics, such as polyphony, pluralism, inclusivity, and the reconciliation of diverse thoughts and cultures. The narrative approach adopted by Ibn al-Daya liberates the story from dogmatism and unilateralism, fostering a pluralistic interpretation and integration of cultural perspectives. This study underscores the significance of examining democratic narratives in classical Arabic literature and their impact on cultural and intellectual integration. The findings contribute to the understanding of how classical Arabic literature can serve as a medium for expressing democratic values and addressing social issues. By providing a democratic perspective within a historical context, Ibn al-Daya's work offers valuable insights into the application of democratic principles in literature, promoting a deeper appreciation for the complexity and diversity of classical Arabic storytelling.